Macmansions, cellars and garrets: Surveying the new Ireland. Issue 1 (23rd June 2013) - Foster, Roy
Abstract : Roy Foster investigates the public response to Ireland's harsh, post‐Celtic tiger existence, and finds more verve and resonance in the nation's proud cultural life than in protest or political change.